Prevalence of Depression Symptoms and its related Factors in School Students - Khadijeh Jahangasht; Shahla Asiri; Sedigheh Pakseresht; Ehsan Kazemnejad Leili (Guilan University of Medical Sciences, 2016)
Abstract Introduction: Health of vision and audition is very effective in physical health and community health nurse plays an important role in the promotion of students health. Therefore studying the visual and auditory health of students by a health nurse can play an important role in the promotion of their health. Objective: This study aimed to determine the visual and auditory health condition of elementary students of Abadan villages. Methods: This cross-sectional descriptive and analytic study consisted of all students studying in 50 schools in primary schools of Abadan villages (5,500 students). Using cluster random sampling method, 26 schools and from each class in every school, 24 students were selected. Finally, 624 students, including 322 girls and 302 boys in age range of 6 to 12 years old in first to sixth grade were enrolled. Data collection tools were Snellen chart and a checklist to record the data. In order to evaluate the auditory health, after training, the student sat against the wall with his/her index finger blocking the ear canal. The researcher stood behind the student and checked right ear, left ear and then both ears by saying two-syllable words. The use of glasses, hearing aids and the eyes and ears were examined and the results were recorded. The validity of the tool was determined by content validity. To determine the reliability, 15 subjects were studied with the tools, twice every other day. The correlation coefficient between the two stages was 1 which showed the reliability of the tool used. Each student was given verbal explanation about the objective and methods of performing the study by the researcher and if content, the students were entered into the study. The data were analyzed by descriptive statistics, measures of central tendency and dispersion, and chi-square with significance level P<0.05. Results: All of students surveyed 20.35 percent (22.98% girls and 17.55% boys) suffered from visual disorder. There was no significant difference between girls and boys (P=0.11). In the meantime 3.04 percent of them wore glasses. Also, 10.10 percent of students (11.80% girls and 8.28% boys) suffered from auditory disorder and there was no significant difference between girls and boys (P=0.18). Conclusion: In attention to study findings, more training on study style, TV watch, importance of wearing glasses and ear health observance especially for girls is necessary. Also referring students with disorder to relevant specialist is important. In this regard, the community health nurse can be very effective.